Myelomeningocele among Pakistani population - Fatima, Urooj; Shabnam Khan; Syeda Urooj Riaz; Hussain Mehdi; Meesam Iftikhar; Nida Fatima (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the mutation in Vangl1 gene in patients of myelomeningocele. Method: The cross-sectional study was conducted from July 2017 to December 2017 in the Dow Diagnostic and Research Laboratory, Karachi, after approval from the ethics review committee of Dow University of Health Sciences, Karachi, and comprised clinically diagnosed infants and 10 healthy individuals from the outpatient department of Jinnah Postgraduate Medical Centre, Karachi. Several anatomical parameters were considered, such as size and site of the cyst. Blood samples were drawn and polymerase chain reaction was conducted for the identification of mutation in Vangl1 gene. Mutation analysis was carried out by aligning the sequence with the reference sequence. Results: Of the 60 subjects, 50(83.3%) were cases with age range 0-10 years, and 10(16.6%) were age matched controls. Majority of the patients 44 (88%) were aged <1 year. Novel mutation in Vangl1 gene was identified at position 239, showing the substitution of valine with glycineV239G. Lumbar region was the most common site for the presentation of myelomeningocele in most of the patients 46(92%). Conclusion: The rare mutation of myelomeningocele was found present in the sample, and the disease was found mostly in the lumbar region. Key Words: Myelomeningocele, Neural tube disorders, Valine, Glycine, Mutation.